The Audio-Lingual Method in Language Teaching - Perdhani, Widya Caterine (Fakultas Ilmu Budaya, Universitas Brawijaya, 2012)
Audiolingualism is a linguistic, or structure-based, approach to language teaching. The starting point is a linguistic syllabus, which contains the key items of phonology, morphology, and syntax of the language arranged according to their order presentation. They may have been derived in part from a Contrastive analysis of the differences between the native tongue and the target language, since these differences are thought to the cause of the major difficulties the learner will encounter.